2022
DOI: 10.1038/s41416-022-01702-z
|View full text |Cite
|
Sign up to set email alerts
|

The association of Health-Related Quality of Life and 1-year-survival in sarcoma patients—results of a Nationwide Observational Study (PROSa)

Abstract: Background Sarcomas are rare cancers of high heterogeneity. Health-Related Quality of Life (HRQoL) has been shown to be a prognostic factor for survival in other cancer entities but it is unclear whether this applies to sarcoma patients. Patients and methods HRQoL was prospectively assessed in adult sarcoma patients from 2017 to 2020 in 39 German recruiting sites using the European Organisation for Research and Treatment of Cancer Quality of Life Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…(Hudson al., 1990;Bacci et al, 2000) A study showed that quality of life could be an independent prognostic factor for survival in osteosarcoma patients. (Eichler et al, 2022) In this study, the average physical and mental components were 49.76±14.33 and 49.01±14.67. Some studies use a score above 50 to be interpreted as a good quality of life and a score below 50 to be interpreted as poor quality of lif e. (Modersitzki et al, 2014) The average results obtained in this study are classified as poor results.…”
Section: Discussionmentioning
confidence: 52%
“…(Hudson al., 1990;Bacci et al, 2000) A study showed that quality of life could be an independent prognostic factor for survival in osteosarcoma patients. (Eichler et al, 2022) In this study, the average physical and mental components were 49.76±14.33 and 49.01±14.67. Some studies use a score above 50 to be interpreted as a good quality of life and a score below 50 to be interpreted as poor quality of lif e. (Modersitzki et al, 2014) The average results obtained in this study are classified as poor results.…”
Section: Discussionmentioning
confidence: 52%
“…The PROSa study is one of the largest prospective observational studies in sarcoma patients published thus far [ 43 , 44 , 45 ]. Cases from 39 study centers encompassing hospitals of maximum care as well as community hospitals and private practices were included.…”
Section: Discussionmentioning
confidence: 99%
“…However, in analogy to the limited experience of primary and secondary healthcare providers with STSs, which can prolong diagnostic intervals and delay specialist referrals, plastic and reconstructive surgery services are not ubiquitously available [ 40 , 41 , 42 ]. The aim of this present analysis was therefore to evaluate the state of accessibility of microvascular reconstructive surgery as well as its role and potential impact on the quality of medical care amongst the participants of the prospective nationwide PROSa (patient-reported outcome measures in sarcoma patients treated between 1984 and 2019) cohort study, which was conducted between September 2017 and February 2019 in 39 German study centers (ClinicalTrials.gov Identifier: NCT03521531), the data from which have previously been published elsewhere [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…We excluded individuals who were mentally or linguistically unable to complete questionnaires in German. Patients were recruited within the PROSa-cohort study (Burden and Medical Care of Sarcoma in Germany: Nationwide Cohort Study Focussing on Modifiable Determinants of Patient-Reported Outcome Measures in Sarcoma Patients), [16][17][18] that was conducted in 39 study sites between 2017 and 2020 (NCT03521531; ClinicalTrials.gov).…”
Section: Methodsmentioning
confidence: 99%